Developing a macro-micro model for analyzing gender impacts of public policy - Jérôme De Henau; Susan Himmelweit (Levy Economics Institute of Bard College, 2020)
This paper discusses new methods of combined macro-micro analysis of labor demand and supply to investigate the gender impacts of public policy. In particular it examines how studies have used input-output analysis together with more or less sophisticated methods of allocating people to jobs to model the impact of public investment in care on the gender employment gap and other inequality measures. It presents some results of a cross-country comparison of investment in the care and construction industries, suggesting methodological refinements to take account of the labor supply effects of such investment policies in order to enable a more detailed analysis of who gets the jobs generated and under what conditions of employment to achieve a more accurate assessment of a policy's full impact on employment inequalities. We argue that such a microsimulation of who is likely to get any newly created jobs should be able to take account of the (child)care "tax" paid by those with caring responsibilities on time spent in employment (as well as the formal tax and benefit system).
Keywords: E17; J16; J21; R15; 330; Care; Microsimulation; Public Investment; Labor Demand; Gender